Effect of different extracts of Aloe Vera gel (Aloe Barbadensis) on blood glucose level of alloxan induced hyperglycaemic mice - Haque, Shammin; Ara, Ferdous; Iqbal, Md Jalaluddin; Islam, Sheikh Nazrul (Bangladesh Medical Journal, 2016)
This study was conducted to evaluate the effect of different extracts of Aloe Vera gel in alloxan induced hyperglycaemic mice.Three different extracts of Aloe Vera gel (dried extract, ethanolic extract and fresh raw extract) were orally administered at 300 mg/kg body weight for 28 days. The fasting blood glucose level was estimated both in normal and alloxan induced hyperglycaemic mice. It was found that, when compared with the control, there was a significant reduction in blood glucose level in all three experimental groups. Ethanolic and fresh raw gel extracts were more effective than the dried extract. The extracts produced similar results when compared with gliclazide. It can be concluded that, the administration of Aloe Vera gel extract significantly decreases blood glucose level in hyperglycaemic mice. Aloe Vera gel can therefore be a natural remedy and a cost effective resource for the management of diabetes. Bangladesh Med J. 2015 May; 44 (2): 61-66